1992
DOI: 10.1080/01459740.1992.9966077
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and risky sex: In search of an elusive connection

Abstract: Since the publication of the 1986 article by Stall, McKusick, Wiley, Coates and Ostrow, the conclusion that drinking alcohol prior to or during erotic encounters increases the probability of engaging in high-risk sexual behavior has been widely accepted, despite some contradictory findings from research on this hypothesis. This paper presents the results of tests of the alcohol/risky-sex hypothesis in a cohort of gay men in Flanders, Belgium. Failing to find evidence to support the hypothesis of a general effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Notably, the findings from this literature have been inconsistent, with some studies finding a statistical relationship between drug or alcohol use during sexual activity and the likelihood of participating in high risk sexual activity among gay men (e,g, StaU et al, 1986;McCusker et al, 1990) while other studies have not found evidence of this relationship even within the same study population (e.g. Bolton et al, 1992;Weatherbum et al, 1993), Nonetheless, four prospective studies have shown that heavier drug or alcohol consumption patterns are significant predictors of incident HIV infections among gay and bisexual men (Burcham et al, 1989;Silvestre et al, 1989;Penkower et al, 1991;Seage et al, 1992), To date, attempts to reconcile the inconsistencies in the behavioral literature have centered on the question of whether any correlation between substance use and high risk sex exists at all, rather than on exploring what might be learned from variation in findings across studies. For example, one source of this divergence in findings is the use of varying methodological approaches to the measurement of sex imder the influence of substances.…”
mentioning
confidence: 62%
“…Notably, the findings from this literature have been inconsistent, with some studies finding a statistical relationship between drug or alcohol use during sexual activity and the likelihood of participating in high risk sexual activity among gay men (e,g, StaU et al, 1986;McCusker et al, 1990) while other studies have not found evidence of this relationship even within the same study population (e.g. Bolton et al, 1992;Weatherbum et al, 1993), Nonetheless, four prospective studies have shown that heavier drug or alcohol consumption patterns are significant predictors of incident HIV infections among gay and bisexual men (Burcham et al, 1989;Silvestre et al, 1989;Penkower et al, 1991;Seage et al, 1992), To date, attempts to reconcile the inconsistencies in the behavioral literature have centered on the question of whether any correlation between substance use and high risk sex exists at all, rather than on exploring what might be learned from variation in findings across studies. For example, one source of this divergence in findings is the use of varying methodological approaches to the measurement of sex imder the influence of substances.…”
mentioning
confidence: 62%
“…Because alcohol expectancies can be acquired vicariously and through various media (Goldman, Brown, & Christiansen, 1987), delivering a message that alcohol use causes riskier sexual behavior may have the effect of "teaching" sexrelated alcohol expectancies to those who may not have previously held them, and reinforcing such expectancies where they already exist. This could have the effect of giving some people an excuse for engaging in unsafe behavior when drinking (Bolton, Vincke, Mak, & Dennehy, 1992). This is especially important given the results of laboratory studies that have highlighted the importance of sex-related alcohol expectancies (e.g., Gordon et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that alcohol or drug use is positively associated with (3)(4)(5)(6)(7)(8)(9)(10), is not related to (11)(12)(13), and inhibits high-risk sexual behavior (14). The inconsistency of findings may be due in part to differences in the types of substances and HIV-related risk behaviors examined, the study approaches chosen and their methodological rigor, and characteristics of the populations studied.…”
mentioning
confidence: 99%
“…Similarly, global association studies of a variety of other populations [e.g., gay men, residents of innercity neighborhoods, and clients of substance abuse treatment centers and sexually transmitted diseases (STD) clinics] have shown associations between general measures of substance use (e.g., lifetime behaviors) and nonuse of condoms (3)(4)(5)10), although some have found no associations (11)(12)(13)(14). The major limitation of these studies is that they do not assess the use of substances in conjunction with sexual activity, and therefore are unable to provide evidence of a direct association between substance use and risky sexual behavior.…”
mentioning
confidence: 99%